Application of the boyer moore method in the application dictionary of web-based information technology terms (case study: pt. erefka tiga pilar utama) - Arini Arini; Hendra Bayu Suseno (INTEGRATED (Journal of Information Technology and Vocational Education), 2022)
The emergence of many new terms in information technology because of the rapid development of technology makes people, especially those who pursue the IT field, must know and learn terms related to information technology. Therefore we need the availability of an information technology dictionary. Dictionary of the term information technology that circulates a lot in the form of printed media / books. However, dictionaries in the form of print media have a weakness in the form of a search process that takes a long time and cannot be updated at any time, therefore a digital / electronic dictionary exists to overcome this weakness. The dictionary application of the term information technology by applying the Boyer Moore algorithm in the search for the term word can help it. The Boyer Moore algorithm applies the good suffix principle where the character being searched for is parallel to the like character, as well as the principle of a bad character where if the character does not have similarities, it is immediately eliminated. The field used in this search is the word term, by entering the term search term as input in the search column, then we can find out the meaning of the term word. The results of this application display the entire pattern that matches the text, with a total search time below 300 milliseconds.